2022
DOI: 10.34142/hsr.2022.08.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Functional condition of students with different types of posture

Abstract: Purpose: The purpose of the work is to conduct a comparative analysis of the functional state of students with different types of posture. Material and methods. The study surveyed 222 students (108 boys and 114 girls). The analysis of the obtained data indicates that only 19.4% of boys and 12.3% of girls have a normal posture. Results. Among students with postural disorders, scoliotic (asymmetric) posture is most common (34.3% of boys and 43.8% of girls), less with stooped (22.2% and 23.7%, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…Функціональні порушення, захворювання та травми опорно-рухового апарату досить поширені серед різних груп населення і характеризуються негативними наслідкамивід зниження працездатності до повної її втрати [4,12].…”
Section: вступunclassified
See 2 more Smart Citations
“…Функціональні порушення, захворювання та травми опорно-рухового апарату досить поширені серед різних груп населення і характеризуються негативними наслідкамивід зниження працездатності до повної її втрати [4,12].…”
Section: вступunclassified
“…За даними медичної статистики в Україні спостерігається невтішна тенденція до зростання поширеності захворювань кістково-м'язової системи [12]. У структурі хвороб кістково-м'язової системи серед дорослого населення переважають деформівні дорсопатії та артрози, а у дітей порушення постави [4,17].…”
Section: вступunclassified
See 1 more Smart Citation
“…Because the students are spending many hours in the same position while studying using the computer or cell phone, they have high risks for posture deficits, spine diseases, and limited range of motion [3]. A study reported that only 19.4% of boys and 12.3% of girls had good study posture [4]. Therefore, various factors can influence students' posture.…”
Section: Introductionmentioning
confidence: 99%
“…Because the students are spending many hours in the same position while studying using a computer or cell phone, they are at high risk of posture deficits, spinal diseases, and having a limited range of motion [5]. Horodetska and Kuts reported that only 19.4% of boys and 12.3% of girls had a good study posture [6]. Although no evidence suggests that correct posture directly affects students' academic performance, studies have found that physical education and movement-based study programs can positively impact spinal mobility and ROM [7,8].…”
Section: Introductionmentioning
confidence: 99%